Meeting support needs for informal caregivers of people with heart failure: a rapid review. (2nd February 2021) - Carleton-Eagleton, Katherine; Walker, Iain; Freene, Nicole; Gibson, Diane; Gibson, Diane
Abstract: Aims : To explore whether a support-based intervention for informal caregivers of people with heart failure changes their psychosocial and emotional wellbeing. Background Successful self-management of heart failure includes addressing the psychosocial and emotional wellbeing needs of informal caregivers. However, there is limited evidence of how caregivers are supported in this way. Methods and results : A rapid review was conducted searching four electronic databases with restrictions to dates January 1996 – September 2019. Specific inclusion and exclusion criteria were applied, and the first author reviewed articles based on title, abstract and then full text, before articles were assessed for conclusions and outcomes. Six studies met the criteria for review. The key caregiver outcomes were burden, depression/anxiety, and quality of life. Significant reductions in caregiver burden were demonstrated in the three studies that measured this outcome. There were mixed results for the outcome measures of depression/anxiety, as well as quality of life, with some interventions demonstrating either significant reductions in depression or anxiety scores, or increases in quality of life scores. Conclusion : With only six studies included in this rapid review, it is not possible to make any definitive conclusions regarding the success, or otherwise, of interventions for caregivers of people with heart failure to improve their psychosocial and emotional wellbeing. Whilst some papers would tend to suggest that such interventions can reduce caregiver burden, there is a need to interrogate further interventions in this area to fill the current gap in the literature.